New strategies to combat unemployment : especially long-term unemployment in Denmark - Nielsen, Soren P. [Verfasser] (My University, 1992)
"Describes Denmark's new strategies, designed to cope with and overcome long-term unemployment. Since the long-term unemployed (LTU) lack formal education and training, a retraining and temporary job creation scheme has been in operation for the last two years. Reports on research and development in education and training of adult LTUs. Concludes that wider vocational and educational courses, catering for the specific needs of the target group, must be established." (author's abstract) ((en)) Dänemarks neue Strategien sind dazu bestimmt, mit der Langzeitarbeitslosigkeit fertig zu werden und sie zu überbrücken. Da Langzeitarbeitslose Defizite in schulischer und beruflicher Ausbildung aufweisen, sind in den letzten zwei Jahren Umschulungen und Arbeitsbeschaffungsmassnahmen entstanden. Weitergehende Berufs- und Bildungskurse müssen etabliert werden, die sich nach dem spezifischen Bedarf der Zielgruppe richten. (IAB)
Neue Strategien gegen die Arbeitslosigkeit, insbesondere Langzeitarbeitslosigkeit in Dänemark
Keywords: S 1 Stufen der Berufsbildung; Arbeitslosigkeit; Gegenmassnahme; Langzeitarbeitslosigkeit; Umschulung; Berufsbildung